The Classification Of Hadith Is In Terms Of Quantity and Quality Of Sanad - Zikri, Muhammad; Fitriyadi, Muhammad; Yuliharti (Sinergi International Journal of Islamic Studies, 2023)
Hadith as one of the sources of Islamic law is a basis that is often used as the strength of a provision in solving problems, however, the lack of knowledge about the classification of hadith often results in debate, whether it is related to whether or not the hadith used is authentic. The number of hadiths that are frequently used should have a strong review of the quality and quantity of the sanad. With this research, it is hoped that there will be references that can be used as references regarding the quality of the hadiths that will be used, considering that there are many hadiths that sometimes make many people unable to distinguish between hadiths, proverbs or just words in Arabic. This study aims to find out about the classification of hadith in terms of quantity and quality of sanad. The research method used is the study of literature (library research) data collection techniques with documentation. The data analysis technique uses content analysis. The result of this study is that hadith is the second source of religious teachings after the Qur'an. besides that hadith also has a function as an explanation of the verses of the Qur'an. Based on the quantity (number of narrators) or the person who narrated a hadith, it can be divided into mutawatir and ahad hadiths. Meanwhile, in terms of the quality of the hadith, it is divided into three, namely authentic hadith, hasan and dha'if.